Citation analysis of dissertations for collection development. Issue 2 (7th April 2015) - Abeyrathne, Dilani Kanishka
Abstract : Purpose: – This study aims to make recommendations for library collection development because undergraduates expect to satisfy their information need for research activities through library collection. Therefore librarian should assess whether the library is adequately responding their research demands. This can be answered by analyzing citations in the dissertations. Design/methodology/approach: – The study analyzed 8, 224 citations from 204 undergraduate dissertations submitted to the Faculty of Agriculture, University of Peradeniya, Sri Lanka, in 2012. The most cited format was determined. Bradford's law was applied to prepare a ranked list of journals. Accessibility of each core journals was observed and recommendations were made for collection development. Findings: – Journals were the most cited format. Data sets were fit with either the verbal formula or mathematical formula of the Bradford's law. Core journals were determined. Core journals were accessible via number of ways. Some journals are subscribed by the Agriculture or via databases through UGC consortia (through University of Peradeniya's library network) or open access journals. There are several journals in which the free access is available through Sri Lanka Journals OnLine. Based on the results, recommendations were made for collection development. Originality/value: – The paper provides useful insight for collection development for research demand, Agriculture Library, University of Peradeniya, Sri Lanka.